VD_FINDINFO HC / 2011 / 322 vom 7. Juni 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT | 125 CC, 137 CC, 176 al. 1 ch. 1 CC, 271 CPC (CH), 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)